The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae) - Shinohara, Akihiko; Hara, Hideho; Smith, David R. (Zootaxa, 2020)
The Xiphydria annulitibia group is defined to include the following five species from northeastern Asia: X. annulitibia Takeuchi, 1936, from Japan (Hokkaido, Kunashiri Is., Honshu, Shikoku), Korea and Russia (Sakhalin, Primorskij kraj), X. kanba n. sp. from Japan (Hokkaido, Honshu), X. kastsheevi Ermolenko, 1979, from Russia (Primorskij Kraj), X. konishii n. sp. from Japan (Hokkaido, Honshu) and X. melanoptera n. sp. from Japan (Hokkaido). Xiphydria annulitibia is redescribed based on a long series of specimens, including the holotype. Three new species, X. kanba, X. konishii and X. melanoptera, are described and illustrated, and a key is provided for the five species. Xiphydria kastsheevi is excluded from the fauna of Japan. For X. kanba, notes on a rare successful case of branch trapping which yielded 87 adult specimens and observations on the adult emergence from a dead branch and peculiar drumming behavior of the male are given.